Mechanical Design Method and Joint Simulation Analysis of Industrial Robots Based on Trajectory Planning Algorithm and Kinematics - Feng, Fang; Wang, Ning; Du, Qing (EAI Endorsed Transactions on Scalable Information Systems, 2023)
INTRODUCTION: At present, the development level of industrial robots is getting higher and higher, but the research on the involvement of high-level industrial robots as well as trajectory planning algorithms in China is limited. It is increasingly important to integrate the theory of kinematics in the development of industrial robots. Some industrial robots have welding, assembly and other characteristics, and play an immeasurable role in national defence, manufacturing and other fields.OBJECTIVES: With the development of China's industry, the manufacturing industry is changing from traditional manufacturing to intelligent manufacturing. Industrial robots have become an important tool for "intelligent manufacturing" and an important strategic emerging industry to improve the adaptability and competitiveness of the industrial market.METHODS: This paper provides an in-depth study of the mechanical design methodology and joint simulation analysis of industrial robots based on trajectory planning algorithms and kinematics.RESULTS: Research on intelligent observation, virtual reality flight trajectory and autonomous real-time flight trajectory design based on flight trajectory machines, which have made important contributions to the improvement of flight trajectory design. The wide application of industrial robots provides good development opportunities and broad market demand for industrial robot design.CONCLUSION: Since the reform and opening up, China's manufacturing industry has made significant progress in machinery, standardization, automation, informatization and other aspects of industrial production, but the development of China's manufacturing industry faces the problem of labour shortage. An effective way to solve this problem is to innovate, update and modernize the manufacturing industry.
Keywords: trajectory planning algorithm; kinematics; industrial robot; mechanical design